Costs and enforcement of biosafety regulations in India and China. (6th March 2006) - Pray, Carl E.; Ramaswami, Bharat; Huang, Jikun; Hu, Ruifa; Bengali, Prajakta; Zhang, Huazhu
This paper examines the cost of compliance and the enforcement of biosafety regulations in China. Costs were higher in India, and enforcement of regulations was more effective in China. Lower costs in China may be because national companies, government research institutes and foreign firms were all pressing for less costly regulation, while in India there was less pressure by these groups to reduce regulatory costs. Enforcement of regulations was less effective in India because farmers and small seed firms have more influence on policy makers and local agricultural departments are supposed to be enforcing decisions from the environmental ministry.